ANALISIS HUKUM MENGENAI HUKUMAN DENDA DALAM KASUS KEKERASAN SEKSUAL TERHADAP ANAK DILIHAT DARI PERSPEKTIF VIKTIMOLOGI - Liantha Adam Nasution; Ediwarman Ediwarman; Muhammad Ekaputra; Marlina Marlina (Universitas Sumatera Utara, 2018)
ABSTRACT Children as the young generations are the successors to the ideals of the nation’s struggle and are the human resource for the National Development. Every child has equal human right like everyone in general. There are many criminal cases experienced by children causing mental disorders that they can no longer perform their obligations. Law enforcement needs to be conducted to the sexual violence perpetrators so that it will give them deterrence and minimize sexual violence against children. Sentence regulation for the perpetrators of sexual violence against children, besides imprisonment, also applies the sentence to fine which money is automatically put into the State Treasury Fund. The problems of this research are how the criminal sentence to fine is regulated in sexual violence case, what factors cause sexual violence and how the criminal law policy concerning the sentence to fine in the case of sexual violence against children is, and how the efforts of legal protection for the victim in Victimology perspective. Based on the results of the research and the analysis done by the author about the sentence to fine stated in KUHP (the Criminal Code) or the Law that regulates sexual violence against children, in its implementation, Sentence to fine that is retributive is implemented to protect the city today. It puts priority to the sentence and fulfills the rights of the suspect/defendant. Its function mainly stresses on the protection of the suspect/defendant’s prestige and dignity, in KUHP, child protection law, law of eradication of domestic violence and the law on trafficking. The concept applied in the present time does not regulate the sentence to fine that is given to the victim for their protection. If the victims want to obtain compensation, they have to file an application of restitution. This restitution is not to be taken by the victim, but it is kept in the Treasury Fund. Therefore, today concept needs to be amended; the sentence to fine should be restorative, so that it can meet the benefit for the protection of the perpetrator and victim. Keywords: sentence, fine, sexual violence, child, victimology